Morphological and Histological Study of the Lung in the Pterocles alchata - Amar Hussein Abd Ali; Nahla A. Al-Bakri; Noor Mohammed Jaafer Hammodi (Kufa Journal for Veterinary Medical Sciences)
The present study was conducted on the Iraqi Pin-tailed Sandgrouse (Pterocles alchata) to study the lung's morphological description and histological structure. This study was used 5 samples of adult male sandgrouse bird. The birds were dissected. The lungs were removed from the coelomic cavity, cleaned to remove impurities, and photographed to describe their morphological features. The samples were fixed using formalin (10%) solution for 36-48 hours and then preserved in alcohol (70%) to prepare the microscopic slides. The results showed that the lung of the Iraqi sandgrouse bird is red in color, has a trapezoidal shape and has three surfaces (costal, visceral, and vertebral). The costal surface shows ribs impressions that extend from the first rib to the sixth rib. Histologically, the microscopic sections of the pulmonary lobule revealed the presence of primary bronchioles lined with ciliated pseudostratified columnar epithelium, resting on a layer of connective tissue interspersed with plates of hyaline cartilage; this layer is known as the lamina propria with the submucosa. The parabronchi occupy more than half the pulmonary lobule volume and are lined with simple squamous epithelium supported by a layer of loose connective tissue followed by smooth muscle tissue. The parabronchi also include halls known as atria, which open at their ends into cones, which in turn connect to a complex network of bronchial and blood tubules, and these structures forming the tissue responsible for gasexchange. In conclusion, our study shows are similar to those observed in most birds have some difference (in color, shape, surfaces, and histological structure).